The Politics of Home: Power Dynamics in Qaisra Shahraz's Perempuan Suci - Roifah, Miftahur; Inayati, Rif'ah (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
This article explores the multifaceted concept of home as presented by Upstone in The Spatial Politics in the Postcolonial Novel, emphasizing its role as both a physical space and a metaphor for colonialism. Upstone posits that the home operates as an autonomous entity, possessing its own systems of authority and power similar to those found in nations and cities. Within this framework, the article examines the hierarchical relationships that exist in domestic settings, particularly between masters and servants, and between men and women. In Qaisra Shahraz's novel Perempuan Suci, these power dynamics are vividly illustrated, revealing a clear disparity between male and female characters. Men hold dominant positions in the household, while women, including daughters, are subordinated and often subject to oppression. The portrayal of these inequalities highlights the pervasive nature of patriarchal structures and gender politics within the home. Additionally, the article discusses how the relationship between masters and servants further exemplifies the oppressive dynamics at play, leading to practices that can result in violence. Ultimately, the analysis asserts that, despite being removed from external political influences, the home embodies its own complex political landscape, characterized by power relations that echo broader colonial discourses. This study underscores the significance of examining domestic spaces to fully understand the interplay of power, oppression, and gender in postcolonial contexts.